An evaluation of 910 premolars transplanted in the anterior region—A retrospective analysis of survival, success, and complications - Louropoulou, Anna; Andreasen, Jens Ove; Leunisse, Manfred; Eggink, Edwin; Linssen, Marcel; Van der Weijden, Fridus; Barendregt, Dick (Dental traumatology, 2024)
Aim The aim this retrospective analysis was to evaluate the survival, success and possible complications of transplanted premolars to the anterior region subdivided in development stage and patient's age. Materials and Methods The material comprised patients that underwent a tooth transplantation between April 2004 and December 2021. A total of 910 premolars were transplanted in 707 patients. Tooth mobility, oral hygiene, and periodontal parameters were clinically evaluated. Standardized radiographs were used to evaluate pulpal and periodontal healing and root formation. The cumulative survival rate was calculated using the Kaplan–Meier method. Results The data were subdivided in three groups based on the stage of root development and patient's age. The average age at surgery was 16 years. The main indication for transplantation was trauma, followed by agenesis and other indications. Two premolars were lost during the whole observation period. The overall survival and success in the immature premolars group after an observation period of 10 years was 99.8%. The 10‐year survival and success rate when fully developed premolars were transplanted in the anterior region in adolescents were 100% and 96.3%, respectively. In adults, the 10‐year survival and success rate were 87.5%. Conclusion Transplantation of premolars with developing and fully developed roots to the anterior region in children, adolescents, and adults is a predictable treatment modality.